Penerapan Media Matur dalam Peningkatan Hasil Belajar Siswa Sekolah Dasar - Hani Fita Fatimah; Lia Widiastuti; Siti Juliati; Muhammad Alvin; Arief Hidayat Afendi; Kurinih Kurinih (Mathematics Education Study Program, 2025)
Learning in primary schools requires innovative methods to improve students' understanding and motivation to learn. One of the main challenges is the lack of student involvement in the learning process due to the use of conventional methods that are less interactive. This study aims to analyze the effectiveness of MATUR media in improving learning outcomes of grade II students of SDN Terusan 1 Sindang. The method used was classroom action research (PTK) carried out in two cycles, involving observation, interviews, tests, and documentation as data collection techniques. The results showed that the application of MATUR media had a positive impact on improving learning outcomes, with an increase in students' average score from 65.4 in the first cycle to 82.7 in the second cycle. In addition, students' involvement in the learning process increased significantly, as seen from the increased active participation in class discussions and their enthusiasm for the material being taught. MATUR media also proved effective in increasing students' learning motivation, due to the more interesting and interactive presentation of the material. The conclusion of this study confirms that the use of innovative learning media can be a solution in creating a more effective and enjoyable learning environment for elementary school students.